Use of Microprocessor-Based Debug Modules for the Development of GPS (GPRS) and GSM Communication Devices - Omarov, Murad; Suhorukov, Semen; Tsekhmistro, Roman; Shapovalov, Serhii (Kharkiv National University of Radio Electronics, 2021)
This report is devoted to an overview of the technical characteristics and the specifics of the use of modern debugging microprocessor modules for the development of devices for geolocation of objects and data transmission over a mobile communication channel.
Keywords: microcontroller system; RASPBERRY PI; arduino ide; GSM(GPS-GPRS)-module